2019
DOI: 10.31083/j.jin.2019.01.18
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency stimulation of afferent axons alters firing rhythms of downstream neurons

Abstract: J o u r n a l o f I n t e g r a t i v e N e u r o s c i e n c eThis is an open access article under the CC BY-NC 4.0 license (https://creativecommons.org/licenses/by-nc/4.0/) Deep brain stimulation is an emerging treatment for brain disorders. However, the mechanisms of high-frequency brain stimulation are unclear. Recent studies have suggested that high-frequency stimulation might produce therapeutic effects by eliminating pathological rhythms in neuronal firing. To test the hypothesis, the present study inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Conversely, abnormal neural activity, including local field potential and synchronization between neurons, is commonly found in neurological diseases such as Parkinson’s disease and epilepsy in addition to retinal degeneration ( Lian et al, 2003 ; Rubchinsky et al, 2012 ; Wang et al, 2016 ). For therapeutic approaches, various types of electrical stimulation have been attempted, such as closed-loop systems for antiphase LFPs ( Sanabria et al, 2020 ) and high-frequency stimulation above 100 Hz ( Santaniello et al, 2015 ; Ma et al, 2019 ), to suppress aberrant activity in these neuropathological fields. As a breakthrough to overcome low-resolution vision in patients with RP, it may be promising to apply therapies developed in other neurological fields to retinal degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, abnormal neural activity, including local field potential and synchronization between neurons, is commonly found in neurological diseases such as Parkinson’s disease and epilepsy in addition to retinal degeneration ( Lian et al, 2003 ; Rubchinsky et al, 2012 ; Wang et al, 2016 ). For therapeutic approaches, various types of electrical stimulation have been attempted, such as closed-loop systems for antiphase LFPs ( Sanabria et al, 2020 ) and high-frequency stimulation above 100 Hz ( Santaniello et al, 2015 ; Ma et al, 2019 ), to suppress aberrant activity in these neuropathological fields. As a breakthrough to overcome low-resolution vision in patients with RP, it may be promising to apply therapies developed in other neurological fields to retinal degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…The initial 30 s periods of 2 min HFS were not used to analyze unit spikes due to the interference of the stimulationevoked PS [27,30]. The firing rhythms of both types of neurons were examined using the following spectrum of auto-correlograms for binary sequences representing the spike firing of individual neurons [26,33,34]. Firstly, the auto-correlogram of each binary sequence was calculated and normalized by its mean value to eliminate the impact of firing rate.…”
Section: Data Analysis For Unit Spikesmentioning
confidence: 99%
“…DBS typically utilizes high-frequency stimulations (HFS) with a constant pulse frequency in a range of 90-200 Hz [22,23]. Studies have shown that HFS can increase the neuronal firing downstream of stimulation sites through axonal projections and modulate the neuronal firing patterns [24][25][26][27][28]. It has been reported that HFS can also increase the LRTCs in LFP oscillations that represent integrated activity of a population of neurons [29].…”
Section: Introductionmentioning
confidence: 99%